Slovene regional atlases: from SDLA-Ts to SDLA-SI - Cossutta, Rada (Slavia Centralis, 2020)
The paper focuses on the presentation of two Slovene regional dialectological atlases that significantly complement the Friulian atlas ASLEF: Slovene Dialectological Lexical Atlas of the Province of Trieste (SDLA-Ts) (1987) for the Trieste Karst and Slovene Dialectological Lexical Atlas of Slovene Istria (SDLA-SI) (2005–2006) for Slovene Istria. Their realisation undoubtedly represents an important achievement in the field of the dialectal lexis of Primorska, which documented and mapped in the mentioned two volumes.
Keywords: linguistic geography; slovene regional atlases; SDLA-Ts; SDLA-SI; dialectology